Perilaku Masyarakat dalam Pemanfaatan Information and Communication Technology dalam Mendukung Pengembangan Masyarakat Global - A. V. S. Hubeis (Jurnal Komunikasi Pembangunan, 2010)
The role of information and communication technology (ICT) in the process of work simplification and expansion ofaccess to many parties has believed to have changed the communication patterns in the daily community life, andalso to understand that ICT is an important aspect underlying the process of globalization. In this case, thegovernment’s role is very important in implementing the ICT regulation in the public sector. As one of the maininitial foundation, the government has published ITE Law in 2008. The government is also faced with the issue ofdigital divide which can become obstacles in the process of ICT capacity building in Indonesia. The issue ofpreparation of ICT-based human resources, economic development and industry applying ICT as a supportingbusiness process, expanding access to information, cultural and social evolution of government governance areelement factors that are believed to play an important role in the development of ICT-based global society.